A broad specificity nucleoside kinase from Thermoplasma acidophilum. Issue 4 (17th January 2013) - Elkin, Sarah R.; Kumar, Abhinav; Price, Carol W.; Columbus, Linda
Abstract The crystal structure of Ta0880, determined at 1.91 Å resolution, from Thermoplasma acidophilum revealed a dimer with each monomer composed of an α/β/α sandwich domain and a smaller lid domain. The overall fold belongs to the PfkB family of carbohydrate kinases (a family member of the Ribokinase clan) which include ribokinases, 1‐phosphofructokinases, 6‐phosphofructo‐2‐kinase, inosine/guanosine kinases, fructokinases, adenosine kinases, and many more. Based on its general fold, Ta0880 had been annotated as a ribokinase‐like protein. Using a coupled pyruvate kinase/lactate dehydrogenase assay, the activity of Ta0880 was assessed against a variety of ribokinase/pfkB‐like family substrates; activity was not observed for ribose, fructose‐1‐phosphate, or fructose‐6‐phosphate. Based on structural similarity with nucleoside kinases (NK) from Methanocaldococcus jannaschii (MjNK, PDB 2C49, and 2C4E) and Burkholderia thailandensis (BtNK, PDB 3B1O), nucleoside kinase activity was investigated. Ta0880 (TaNK) was confirmed to have nucleoside kinase activity with an apparent KM for guanosine of 0.21 μM and catalytic efficiency of 345, 000 M−1s−1. These three NKs have significantly different substrate, phosphate donor, and cation specificities and comparisons of specificity and structure identified residues likely responsible for the nucleoside substrate selectivity. Phylogenetic analysis identified three clusters within the PfkB family and indicates that TaNK is a member of a new sub‐family with broad nucleoside specificities. Proteins 2013. © 2012 Wiley Periodicals, Inc.